1959
DOI: 10.1161/01.cir.20.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Iproniazid in Angina Pectoris

Abstract: There has beell considerable recent interest ill the treatment of anginla pectoris witlh iproniazid. In this paper the results of a careful double-blind study of its effect are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1960
1960
1966
1966

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In addition the apparent usefulness of iproniazid in the treatment of angina has been severely limited by the development of liver damage, which has been estimated at I out of every 3,000-4,000 cases treated, with a mortality rate of 20-25% (Jolly, 1959). Although Shoskes et al (1959) reported a significant improvement of the symptoms of angina with a low dosage (50 mg. daily) without any incidence of liver damage, other less toxic mono-amine oxidase inhibitors were clearly required (Master and Donoso, 1959). …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition the apparent usefulness of iproniazid in the treatment of angina has been severely limited by the development of liver damage, which has been estimated at I out of every 3,000-4,000 cases treated, with a mortality rate of 20-25% (Jolly, 1959). Although Shoskes et al (1959) reported a significant improvement of the symptoms of angina with a low dosage (50 mg. daily) without any incidence of liver damage, other less toxic mono-amine oxidase inhibitors were clearly required (Master and Donoso, 1959). …”
mentioning
confidence: 99%
“…Allowance has to be made, on the one hand, for the initial improvement to be articipated as a result of the extra care implicit in any clinical trial (Cole et al. 1957), and, on the other hand, for the delay in the effect of mono-amine oxidase inhibitors, which may be as long as 10-14 days after beginning therapy, and which may persist for a similar period after ending therapy (Shoskes et al, 1959;Master and Donoso, 1959). To reduce the effect of these conflicting factors to a minimum in assessing the value of the different types of treatment, it was decided to use only the number of attacks of pain recorded during the last three weeks of each six-week perrod of treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations